‘Where is the Justice?’ Unauthorized Migrants’ Perceptions of the Legitimacy of the Dutch Immigration System - Kox, M. H. (Mieke) (The British journal of criminology, 2025)
The legitimacy of immigration systems in a globalized world is questioned since individuals without legal status are excluded from states’ liberal political projects and presumed to hold beliefs different from those of the state. Drawing on ethnographic research with 105 unauthorized migrants in the Netherlands, this contribution demonstrates that these migrants may consider immigration systems to be legitimate if states lawfully enact them and provide access to their human rights. Yet, they believe that the Dutch authorities currently neglect these obligations, resulting in perceived legitimacy deficits. While some scholars advocate for new vocabulary to better understand these systems, I argue that the focus should be on changing these systems to ensure legitimacy and uphold the liberal principles of democracy.